Ice-riding pinnipeds [electronic resource] : a description of the migration and peculiarities of the Phoca Greenlandica and Cystophora Cristata, with remarks on the Phoca Barbata, the Vitulina, and Trichechus Rosmarus on the north-east coast of America - Robinson, George. (London : J.D. Potter, 1897)
Electronic reproduction. Mode of access: Internet. 44